Effect of breathing conditions on relationships between impairment, breathing laterality and coordination symmetry in elite para swimmers - Seifert, L.; Létocart, A.; Guignard, B.; Regaieg, M. A. (Scientific Reports, 2024)
The aim was to investigate the effect of breathing conditions and swimming pace on the relationships between the impairment, the breathing laterality and motor coordination symmetry in elite front crawl Para swimmers. Fifteen elite Para swimmers with unilateral physical impairment or with visual impairment and unilateral breathing preference performed eight 25 m using four breathing conditions (every three strokes, every two strokes on preferred and non-preferred breathing side and apnea) at slow and fast paces in a randomized order. Multicamera video system and five sensors have been used to assess arm and leg stroke phases and to compute symmetry of arm coordination (SIIdC) and of leg kick rate (SIKR). Our findings emphasized motor coordination asymmetry whatever the breathing conditions and swimming paces, highlighting the influence of impairment. Multinomial logistic regression exhibited a high probability for motor coordination asymmetry (SIIdC and SIKR) to be present in categories of Para swimmers with impairment and breathing laterality on the same side, suggesting the joined effect of unilateral impairment and unilateral breathing. Moreover, unilateral physical impairment and breathing laterality could also occur on different sides and generate motor coordination asymmetry on different sides and different levels (arms vs. legs). Finally, visual impairment seems amplify the effect of unilateral breathing on motor coordination asymmetry.